ANALYZING CONSUMER BEHAVIOR AND MARKETING STRATEGIES FOR GREEN SKINCARE BRANDS IN INDONESIA - Maria Christina; Aurelia Lalita Kirana Jayananda; Raymond Raymond Siregar; Fatik Rahayu (Journal of Social and Economics Research, 2024)
This study examines the impact of brand image and product risk attributes on consumer evaluations of skincare products. The analysis results indicate that the attribute that is the longest and closest to the x-axis is the brand image attribute, thus brand image is referred to as the x-axis. Meanwhile, the attribute that is the longest and closest to the y-axis is the product risk attribute, thus product risk is referred to as the y-axis. Among the six skincare products analyzed, The Body Shop deserves to be said as the market leader because it excels in two main dimensions and is located in the first quadrant (Positive X and Positive Y).